A NEW REPORT OF UNUSUAL PARASITISM OF ASOTANA FORMOSA (ISOPODA: CYMOTHOIDAE) ON SERRASALMUS RHOMBEUS (CHARACIFORMES: SERRASALMIDAE) IN THE UPPER AMAZON RIVER BASIN - Anaguano-Yancha, Fernando (2022)
In Ecuador, knowledge of isopod parasitism on fish is scarce. To date, only five species of Isopoda are known to parasitize fish in the Ecuadorian Amazon. Here, we present records of the first infestation of commensal-host interaction between Serrasalmus rhombeus Linnaeus, 1766 and Asotana formosa Schiödte & Meinert, 1881 in the Ecuadorian Amazon region, based on specimens collected in the Huiririma River, northeastern part of the country. Asotana formosa is located in the mouth cavity of S. rhombeus, where it causes mild lesions in the epithelium. Parasitic intensity was one isopod per host and the prevalence was 3.8 %.